Native sources of Japanese industrialization, 1750-1920 Thomas C. Smith - Smith, Thomas C. (University of California Press, 1988)
Here is a collection of important essays on the demographic, economic, and social history of both the Tokugawa period and the modern era by one of Japan's most eminent historians. Gathered together for the first time, these ten essays provide an introduction to the modernization of the country and, as one critic has said "reflect both a sensitivity to Japanese social character and a sophisticated challenge to universal truths about modern industrial societies and human relations."